The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.jafc.9b03435
|View full text |Cite
|
Sign up to set email alerts
|

Water Solubility and Surface Property of Alkyl Di-/Tri-/Tetraoxyethyl β-d-Xylopyranosides

Abstract: Alkyl di-/tri-/tetraoxyethyl β-D-xylopyranosides as derivatives of alkyl xylosides are a class of non-ionic sugarbased surfactants. They were stereoselectively synthesized by the Helferich method. Their properties including hydrophilic− lipophilic balance number, water solubility, surface property, foam property, emulsifying property, and thermotropic liquid crystal property were mainly investigated. The results showed that their water solubility decreased with increasing the alkyl chain length and increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 70 publications
0
45
0
Order By: Relevance
“…Increasing the hydrocarbon chain length reduces the solubility in water, which is reflected in their foaming ability (Table 2). 34,35 Thus, among the series of amphiphiles, the foaming ability of M12 is excellent and comparable to a widely used commercial detergent sodium dodecyl sulfate (SDS). Hence, M12, a surfactant primarily based on renewable resources, might be a valuable alternative to SDS, which causes undesirable side effects.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the hydrocarbon chain length reduces the solubility in water, which is reflected in their foaming ability (Table 2). 34,35 Thus, among the series of amphiphiles, the foaming ability of M12 is excellent and comparable to a widely used commercial detergent sodium dodecyl sulfate (SDS). Hence, M12, a surfactant primarily based on renewable resources, might be a valuable alternative to SDS, which causes undesirable side effects.…”
Section: Resultsmentioning
confidence: 99%
“…The foam volume (H 5 ) was subsequently rerecorded after being left for 5 min, and the foam vanishing rate (ν) was calculated according to formula 2. 27,28…”
Section: Methodsmentioning
confidence: 99%
“…The theoretical analysis showed that the hydrophilic and lipophilic balance (HLB) number of the longchain glycosides indeed is smaller than the HLB number of the short-chain glycosides such that the long alkyl group would reduce the hydrophilicity and weaken the water solubility and even damage their practical values. 28 As an important part and effective extension of the research project, an oxyethylene fragment as a hydrophilic spacer was already introduced into traditional alkyl β-D-glucopyranosides to successfully obtain alkoxyethyl β-D-glucopyranosides and alkoxyethyl β-D-xylopyranosides with improving related water solubility. 27,28 The research triggered us to take the investigation further.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations